A systematic review of pregnancy-related clinical intervention of drug regimens due to pharmacokinetic reasons - Borda, Lauren A.; Någård, Mats; Boulton, David W.; Venkataramanan, Raman; Coppola, Paola (Frontiers in Medicine, 2023)
Background and objective Published works have discussed the pharmacokinetic interactions of drugs with pregnancy, but none comprehensively identify all the approved United States Food and Drug Administration (FDA) and European Medicines Administration (EMA) drugs that have a pregnancy-related intervention. The objective of this systematic review is to comprehensively identify medications that have clinically meaningful interventions due to pharmacokinetic reasons. Methods An in-depth search of clinical data using the PDR3D: Reed Tech Navigator™ for Drug Labels was conducted from 1 June to 12 August 2022. The PDR3D was analyzed using the search terms “pregnant” and “pregnancy” within the proper label section. Regarding the US labels, the terms were searched under the “dosage and administration” section, whereas with the EU labels, the terms were searched within the “posology and method of administration” section. If a finding was discovered within the search, the rest of the label was analyzed for further information. Clinical relevance was based on whether an intervention was needed. Results Using the search strategy, 139 US and 20 EU medications were found to have clinically meaningful interventions in pregnancy. The most common explanations for clinical relevance included hepatic metabolism, protein binding, renal elimination, and P-gp influence. Of the US labels: 40 were found to undergo hepatic metabolism, 11 were found to be influenced by renal elimination, 12 were found to be influenced by protein binding, 7 were found to be influenced by P-gp, and the remaining drugs required further research. Of the EU labels: 11 were found to undergo hepatic metabolism, 3 were found to be influenced by renal elimination, 3 were found to be influenced by protein binding, 1 was found to be influenced by P-gp, and the remaining drugs required further research. Conclusion This comprehensive review of clinically relevant interventions in pregnancy will potentially aid in the treatment of pregnant females when they are undergoing therapy, provide intervention and dosing guidance for physicians, and save time for prescribers and pharmacists. Advances in non-clinical predictions for pregnancy dosing may guide the need for a future clinical evaluation.